In Chemical and Biochemical Processes, Fault Detection and Diagnosis: A Review Study: Exploring Fault Detection and Diagnosis in Chemical and Biochemical Processes (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Biochemical and chemical processes are gaining industrial popularity due to inherent advantages such as mild working conditions and process flexibility, which means lower operating costs due to lower energy needs and a variety of industrially relevant goods that can be generated from a general process setup. Because of these characteristics, biochemical processes have been the focus of intensive study in the medicinal, fine chemical, and bioactive portion sectors. There is a wealth of knowledge available in the literature on fault identification and diagnostic (FDD) strategies for traditional chemical processing plants. The applicability of FDD techniques to biochemical and chemical processes is discussed in this paper.